REVIEW OF IPOMOEA PES-TIGRIDIS L.: ETHNO BOTANICAL CHARACTERISTICS, PHARMACOLOGICAL ACTIVITIES - Venkateshan, N.; Subramaniyam, M.; Santhanakumar, M. (International Journal of Current Pharmaceutical Research, 2018)
Nowadays there is a need for scientific justification of plants that have been used in traditional medicine because of loss of information, improvement of therapy and deforestation that is taking place. The majority of the natural products are compounds biosynthetically derived from primary metabolites and are generally categorized as secondary metabolites. These are the major sources of the pharmaceutical industry to discover novel drugs. The basis for interest in natural product chemistry serves as a lead compound for newer drugs, give as much information on possible mechanism and thus on the molecular origin and basis of diseases. Natural products are permanent challenges with respect to total synthesis and stimulate the development of new reagents and reactions. The present study has been taken up to review one of the ethno medicinal significant of Ipomoea pes-tigridis L plant belonging to the family convolvulaceae. The ethno medical information of the plant reveals that the herb Ipomoea pes-tigridis Linn was used as an antidote to dogbite, boils and carbuncles, the leaves were applied as a poultice for boils, carbuncles and sores. The root of this plant was found to possess purgative action. The phytochemical studies on the leaves have been reported for the presence of carbohydrates, proteins and resins.